INDEPENDENSI PENGURUS PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) DALAM HUKUM KEPAILITAN - Kheriah ' (Fakultas Hukum Universitas Riau, 2013)
Suspension of payment is a way toavoid the company from brankruptcyproceedings. PKPU an independentdetermination of the board and has noconflict of interest between debtor andcreditors is very difficult to determinebecause of the absence of strict rules.PKPU board in carrying out isauthority can not be separated fromcooperation with the managementcompany that is cooperative and noncooperative wich can pose an opstacleto the succest of the proses PKPU. Thisstudy aims to determine the setting ofboard independence and authorityrelations between PKPU with themanagement companys board and theobstacles faced by the board PKPUagainst debtor property.Key words: Suspension of payment ,The board PKPU and Propertycompanies.